Multimedia Audio Visual And Broadcasting Bagian Detik TV PT. Agranet Multicitra Siberkom Jakarta Selatan - Jendi Suryadi; Muhammad Arief; Winoto Winoto (UNIVERSITAS RAHARJA, 2017)
The rapid development of technology in the current era of globalization makes a handful of people need to get more information, in order to add insight. No doubt the need for information becomes a necessity. News is an information about the occurrence of an event or event. Its development through radio broadcasting, print media, television broadcasting and online media. Online news broadcasting is a package that must be packaged well and good for people who watch it get the latest and actual information. An online news broadcasting package includes activities to be Reporter, Editing related to production and packaging in News delivery in PT. AGRANET MULTICITRA SIBERKOM (detikcom).